Association of the Human Bocavirus With Tonsil Squamous Cell Carcinomas - Höpken, Merle; Förster, Isabel; Maune, Steffen; Brockmann, Michael; Schildgen, Oliver; Schildgen, Verena (Frontiers in Microbiology, 2018)
Background The human bocavirus (HBoV) is known to persist latently in the infected host cells and seems to replicate its DNA via the DNA damage response system, which is frequently defect in tumours and correlates with microsatellite instability (MSI). Because HBoV is able to persist in the infected tissues, induces pro-fibrotic and pro- cancerogenic cytokines in vivo and in vitro, and is detected in colorectal and lung tumors, the virus may be involved in cancerogenesis at least as a cofactor. Recently it was shown that the adenotonsillar tissue is an important site of HBoV1 persistence and replication. Considering the background that approximately 60% of oropharyngeal cancers were thought to be attributable to a HPV infection, a co-participation of HBoV in terms of a chronic virus infection might play a role in the cancerogenesis of tonsil tumors. Methods Formalin-fixed, paraffin-embedded tonsil tumor samples were screened for HBoV and HPV DNA. Positive tissue sections were afterwards subjected to fluorescence in situ hybridization (FISH) analysis to identify HBoV and HPV infected cells. By use of an in vitro cell culture model with primary tonsil fibroblasts, keratinocytes, and lymphocytes infected by HBoV we tried to find the target cells of virus replication. MSI testing was based on a previously published protocol using a de-multiplexed PCR followed by fluorescent detection of PCR products in a capillary sequencing device. Results In total 62 of 103 (60,19%) tonsil squamous cell carcinomas tested positive for HBoV-DNA, 66 of 103 (66%) samples were identified as HPV-positive. The FISH analysis revealed both double infection of HPV and HBoV in the same cells as well as single infections of both viruses within the tumor tissue. Twenty-two of 62 HBoV-positive tumors tested HPV-negative, 40 of 62 tissue sections were HBoV and HPV positive. We analyzed 21 out of the 62 HBoV--positive tumors for MSI. Of those four tonsils displayed MSI in at least one of ten microsatellite markers. Conclusions Our findings support the hypothesis that human bocavirus infections as a cofactor may have an impact on tumor development in tonsils, although it still remains possible that HBoV solely displays a tumor tropism.